Do polyphenols affect body fat and/or glucose metabolism? - Alqarni, Saleha; Alsebai, Mashael; Alsaigh, Batool Adal; Alrashedy, Abeer Sayer; Albahrani, Israa Talal; Aljohar, Albandri Yousef; Alazmi, Amjad Obaid (Frontiers in Nutrition, 2024)
Background: Obesity is reaching epidemic proportions with 51% of the population expected to be obese by 2030. Recently, polyphenols have been highlighted as an effective approach to managing obesity and associated risks. Polyphenols are a large class of bioactive plant compounds classified into two major categories: flavonoids which are distinguished by the fundamental C6-C3-C6 skeleton and non-flavonoids .Objective: This systematic review evaluated the effect of different polyphenol sources in overweight and obese people with and without type 2 diabetes. The primary outcome was lipid profile and the secondary outcomes were blood glucose, HbA1c (%), HOMA-IR, weight, and body mass index.Method: A search was undertaken in PubMed, Web of Science, Medline, and Wiley for randomised control trials that assessed different sources of polyphenols in overweight and obese people with or without type 2 diabetes. The quality of the included studies was assessed using the National Heart, Lung, and Blood Institute Quality Assessment Tool.The search yielded 935 studies, of which six randomised control trials met the inclusion criteria. Five studies found no significant difference in lipid profile between the control and intervention groups in triglycerides, total cholesterol, LDL cholesterol, and HDL cholesterol.However, one study showed significant differences in triglycerides (P = 0.04) and HDL cholesterol (P = 0.05) between the two groups with no significant difference in total cholesterol and LDL cholesterol. There were no significant changes in blood glucose observed in the included studies, with only two studies reporting a significant difference in A1c between the groups. Four studies found no difference in HOMA-IR, while one study showed a significant decrease in HOMA-IR in the intervention group compared to the control group. Three studies reported no difference in BMI or weight between the two groups.The data associated with the specific health benefits of polyphenols and their sources in people with overweight, obese, and type 2 diabetes are still limited, so further research is required to support their use and prove their benefits.